2006
DOI: 10.1111/j.1365-2958.2006.05464.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensing DNA methylation in the protozoan parasite Entamoeba histolytica

Abstract: SummaryIn the protozoan parasite Entamoeba histolytica, 5-methylcytosine (m5C) was found predominantly in repetitive elements. Its formation is catalysed by Ehmeth, a DNA methyltransferase that belongs to the Dnmt2 subfamily. Here we describe a 32 kDa nuclear protein that binds in vitro with higher affinity to the methylated form of a DNA encoding a reverse transcriptase of an autonomous non-long-terminal repeat retrotransposon (RT LINE) compared with the non-methylated RT LINE. This protein, named E. histolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 61 publications
(84 reference statements)
0
49
0
Order By: Relevance
“…In E. histolytica, 5-methylcytosine modifications have been confirmed, an active DNA methyltransferase has been reported (44), and an E. histolytica methylated LINE binding protein that binds preferentially to methylated DNA has been characterized (45). In addition, histone acetylation and deacetylation are operational in E. histolytica (46).…”
Section: Discussionmentioning
confidence: 99%
“…In E. histolytica, 5-methylcytosine modifications have been confirmed, an active DNA methyltransferase has been reported (44), and an E. histolytica methylated LINE binding protein that binds preferentially to methylated DNA has been characterized (45). In addition, histone acetylation and deacetylation are operational in E. histolytica (46).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to bacterial DNA, E. histolytica DNA has an AT-rich (75.3%) genome and CG dinucleotides are underrepresented (22). It has been reported that E. histolytica has a DNA methyltransferase of the DNMT2 family which targets rRNA (29). Methylation seems to occur mostly at AT dinucleotides and not at the common CpG site as in vertebrate systems (5).…”
Section: Discussionmentioning
confidence: 99%
“…For Western blotting, nuclear fractions of pJST4-Ehmeth-or pcontrol-transformed E. histolytica trophozoites were prepared using a previously described protocol (24). Proteins were resolved on 12% SDS-polyacrylamide gel electrophoresis gels and then transferred to nitrocellulose membranes.…”
Section: Methodsmentioning
confidence: 99%